Factors associated with hospitalization of people with influenza in a Malaysian tertiary hospital from 2015 to 2019 - Rakhee Yadav Hematram Yadav; Nithiah Thangiah; Karumathil Sharmila Bhaskaran; Chitra Kumarasamy; Shathanapriya Ammikapathi; Jean Khor; Sanjay Rampal (PLoS ONE, 2025)
Influenza contributes substantially to global morbidity and mortality. While most individuals recover from influenza without complications, certain groups are at higher risk of developing severe illness requiring hospitalization. This retrospective cohort study investigated the plausible determinants of hospitalization and its duration among participants who tested positive for influenza A or B. A hospital-based study was conducted in Selangor, Malaysia from 1 January 2015 until 31 December 2019. Sociodemographic characteristics, laboratory investigations, clinical signs and symptoms, and comorbidities were extracted from the hospital’s electronic medical records. Binary logistic and multiple linear regression were used to model the odds of hospitalization and duration of stay, respectively, stratified by age (<18 and ≥ 18 years). A total of 2,593 participants comprising 1,420 < 18 and 1,173 ≥ 18 years were included. Among <18, the odds of hospitalization were higher among those aged under 5 compared to 5–17 years, Malays compared to Chinese, and those with fever, cough, and chest x-ray. Hospitalization duration was higher among Malays and Indians compared to Chinese children, and those with fever, cough and chest x-ray. Among adults, those aged 18–39 years compared to 40–59 years, Malays and Indians compared to Chinese, those with a history of fever, cough, sore throat and chest x-ray were more likely to be hospitalized. The duration among ≥ 18 years was higher among those ≥60 years, chest x-ray, and females. Participants under 5 years are more likely to be hospitalized and those aged 60 and above were more likely to have longer hospital duration compared to all other ages and may benefit more from primary prevention activities such as vaccination. The heterogeneous associations between the risk factors for hospitalization and hospital duration highlight the need for further research. Better risk stratification of influenza patients may better mitigate the impact of influenza A and B.